KEVALIDAN MEDIA PERMAINAN ENGKLEK PADA MATERI SISTEM ORGANISASI KEHIDUPAN KELAS VII SMP GUPPI SAMATA - Urbatul Aenia; Andi Maulana; Hamansah Hamansah (Al-AHYA: Jurnal Pendidikan Biologi, 2021)
The purpose of this study was to determine the validity of the engklek game media on the material organization system of life for class VII SMP Guppi Samata. This study uses research and development methods with a 4D development model, namely definition, design, development, and dissemination. However, product trials to test practicality and effectiveness were not carried out due to the Covid-19 pandemic. The product is validated by 2 experts. The results of the validity analysis show that the engklek game media material for the life organization system developed has a validity level based on the assessment of experts, which is 3.23 and is included in the valid category so it is feasible to use. This research implies that the engklek game media deserves to be used as a learning medium, especially in the material of life organization systems, to further researchers, it should be able to produce better learning media products